2022
DOI: 10.3390/md20050324
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Natural Deep Eutectic Solvents and Extraction Method on the Co-Extraction of Trace Metals from Fucus vesiculosus

Abstract: In recent years, natural deep eutectic solvents (NADES) have been widely investigated for the extraction of food and medicinal plants as well as seaweeds. However, the ability of NADES for trace elements co-extraction from natural sources is not well investigated. The aim of this study was to investigate the ability of common NADES for trace elements co-extraction from Fucus vesiculosus. All of the tested NADES did not recover As and Co (concentration <LOQ). Moreover, all of the tested NADES provided a low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…For the evaluation of the accuracy of the method, a reference sample of Cu was added to the F. distichus sample as described in [ 41 ]. The mean recovery value of Cu was 94–104%.…”
Section: Methodsmentioning
confidence: 99%
“…For the evaluation of the accuracy of the method, a reference sample of Cu was added to the F. distichus sample as described in [ 41 ]. The mean recovery value of Cu was 94–104%.…”
Section: Methodsmentioning
confidence: 99%
“…Medicinal plants can accumulate a high amount of trace elements due to the industrial load on the environment, which are transferred with solvents from the plant material to the extract [158,159]. In the work of Shikov et al, acid-based NaDESs (polar solvents) are seen as an alternative to co-extract trace elements from the roots of this plant [160][161][162]. Five NaDESs were used to co-extract trace elements and glycyrrhizic acid (GA, one of the key active principles in licorine and the dominant phytochemical in the plant) from the roots of G. glabra and, due to similarities in the pKa of tactic acid and GA, the yield of GA in lactic acid-based NaDESs was higher in comparison with the other NaDESs.…”
Section: The Beauty Of Science: the Fascinating Intersection Of Nades...mentioning
confidence: 99%
“…the isolation of natural products from medicinal plants[148] Choline chloride:malonic acid Choline chloride:malic acid Choline chloride:tartaric acid Choline chloride:citric acid 1with 30% water addition)Alternative for co-extracting trace elements from the roots of Glycyrrhiza glabra L [160][161][162]. Lactic acid:glucose:water Choline chloride:lactic acid Choline chloride:malic acid 5…”
mentioning
confidence: 99%
“…Recent research demonstrated that there was no health or carcinogenic risk following topical application of the tested NaDESs, with the calculated daily intake of trace elements from the NaDES extracts being below the daily dose risk estimators. This suggests that NaDESs can have yet another important advantage over other solvents [ 30 ]. For this purpose, Lakka et al [ 31 ] performed an NaDES extraction technique assisted by a batch-stirred tank extractor, using as a naturally derived solvent a eutectic mixture of L-lactic acid (HBD) and glycine (HBA) (5:1 ratio), which proved to be green and efficient.…”
Section: Introductionmentioning
confidence: 99%